A Theoretical Study on Reluctant Staying in the Workplace - Masahiro YOSHIZAKI (AAOS Transactions)
The aim of this paper is to theoretically examine the structures that give rise to reluctant staying in the workplace, focusing on the individual's intention regarding career choice. In existing research, individuals who remain in an organization despite having the intention to leave are referred to as reluctant stayers. Previous research on individuals in this situation has attempted to identify antecedents that lead to the intention to leave, focused on the effects on the organization, and attempted to clarify the situation of unwillingness to remain by comparing it to those who remain because they want to. However, the accumulation of studies explaining the mechanisms that give rise to unwillingness to remain and the reasons why such conditions persist is not sufficient. Therefore, this study examines the research potential of reluctant staying in the workplace in the theory of organizational behavior, focusing on the individual's willpower that cannot resolve unwillingness.